AZV design works vol 4. - Mahmud, Shahril Anwar; Zolkefli, Megat Faridrullah; Ahmad, Afiqah; Jamel, Nurul Shafienaz; Mos, Mitchell Tony; Sebri, Nur Izzati; Hashim, Mohd. Iqbal (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Architecture is a discipline that merges imagination with technical expertise, and the works featured in these pages are a testament to the exceptional talent, perseverance, and vision of our students. With innovative thinking and bold perspectives, they have pushed the boundaries of design and explored the transformative potential of architecture. Their projects not only demonstrate strong technical and artistic skills but also reflect a deep commitment to creating meaningful contributions to society, particularly within the distinctive context of Borneo.